The Association of Suppressed Hypoxia-Inducible Factor-1 Transactivation of Angiogenesis With Defective Recovery From Cerebral Ischemic Injury in Aged Rats - Guo, Yingjia; Zhou, Junpeng; Li, Xianglong; Xiao, Ying; Zhang, Jingyao; Yang, Yutao; Feng, Li; Kang, Y. James (Frontiers in Aging Neuroscience, 2021)
Elderly patients suffer more brain damage in comparison with young patients from the same ischemic stroke. The present study was undertaken to test the hypothesis that suppressed hypoxia-inducible factor-1 (HIF-1) transcription activity is responsible for defective recovery after ischemic stroke in the elders. Aged and young rats underwent 1-hour transient middle cerebral artery occlusion (MCAO) to produce cerebral ischemic injury. The initial cerebral infarct volume in the young gradually declined as time elapsed, but in the aged rats remained the same. The defective recovery in the aged was associated with depressed angiogenesis and retarded neurorestoration. There was no difference in HIF-1α accumulation in the brain between the two age groups, but the expression of HIF-1 regulated genes involved in cerebral recovery was suppressed in the aged. In confirmation, inhibition of HIF-1 transactivation of gene expression in the young suppressed cerebral recovery from MCAO as the same as that observed in the aged rats. Furthermore, a copper metabolism MURR domain 1 (COMMD1) was significantly elevated after MCAO only in the brain of aged rats, and suppression of COMMD1 by siRNA targeting COMMD1 restored HIF-1 transactivation and improved recovery from MCAO-induced damage in the aged brain. These results demonstrate that impaired HIF-1 transcription activity, due at least partially to overexpression of COMMD1, is associated with the defective cerebral recovery from ischemic stroke in the aged rats.